Vision screening for frail older people: a randomised trial. Issue 6 (9th July 2008) - Swamy, B; Cumming, R G; Ivers, R; Clemson, L; Cullen, J; Hayes, M F; Tanzer, M; Mitchell, P
Abstract : Aim: To assess the effects of vision screening, and subsequent management of visual impairment, on visual acuity and vision-related quality of life among frail older people. Design: Randomised controlled trial. Setting: Community in Sydney, Australia. Participants: 616 men and women aged 70 years and over (mean age 81 years) recruited mainly from people attending outpatient aged care services. Control: No vision assessment or intervention Interventions: Comprehensive vision and eye examinations conducted by an optometrist. Three hundred subjects were seen by the study optometrist, with 146 judged to need treatment for a vision or eye problem. The optometrist arranged new glasses for 92 subjects; 24 were referred for a home visit by an occupational therapist; 17 were referred for glaucoma management; and 15 were referred for cataract surgery. Main outcome measure: Distance and near visual acuity (logMAR) and composite scores on the 25-item version of the National Eye Institute Visual Function Questionnaire, both assessed at a 12-month follow-up home visit. Results: After 12 months' follow-up, the mean (logMAR) distance visual acuity was 0.27 in the intervention group and 0.25 in the control group (p = 0.32). The mean (logMAR) near visual acuities were −0.01 in the intervention group and −0.03 in the control group (p = 0.26). The mean composite score on the National Eye Institute Visual Function Questionnaire was 84.3 in the intervention group and 86.4 in the control group (p = 0.49). Conclusions: Vision screening by an optometrist for frail older people living in the community in Australia does not lead to improvements in vision or vision-related quality of life after 1 year's follow-up.